Lymph node density in muscle-invasive transitional cell carcinoma of the urinary bladder; De novo versus progressive disease - Elabbady, Ahmed; Hashad, Mohamed Mohieeldin; Kotb, Ahmed Fouad; Abdullah, Dina Mohamed; Beltagy, Ahmad (International Journal of Health Sciences, 2017)
Objective: The prognosis of bladder cancer patients with positive lymph node (LN) disease is affected by both the extent of lymphadenectomy and LN density retrieved during radical cystectomy. This study aimed at assessing the differences in LN metastasis between patients who presented primarily with muscle-invasive transitional cell carcinoma of the bladder “de novo disease” versus “progressive disease.” The latter is defined as patients who progressed to muscle-invasive bladder cancer (MIBC) following prior conservative management of a non-muscle-invasive disease. Methods: Data were prospectively collected from consecutive 41 radical cystectomies that were divided into two groups: Group I included de novo MIBC cases and Group II included progressive MIBC cases. Results: The median age was 60 years (44-75). Thirty-four patients exhibited de novo disease versus 7 patients who presented as progressive MIBC with a median duration of 9 months between the resection of the first non-invasive tumor and the diagnosis of progressive MIBC (range: 6-56 months). The median number of retrieved LNs in both groups was 15 LNs (range: 4-36). Ten patients (24.39%) had positive pathological LN disease; distributed as 9 patients in Group I and 1 patient in Group II. The median LN density of LN-positive patients was 15.73% (6.46 % in Group I, 28.57% in Group II). Five patients had LN density >20%. Conclusion: Although non-muscle-invasive urothelial bladder tumor may progress to muscle-invasive disease, it still carries less aggressive course than de novo MIBC based on differences in LN metastasis and density.